Penguatan Pendidikan Islam Bagi Muslim Minoritas di Lingkungan Non-Muslim (Studi Kasus di Sengkan Condongcatur Depok Sleman) - Safi'i, Ahmad (Jurnal Tarbiyatuna, 2019)
Sengkan, Condongcatur, Depok, Sleman is inhabited by 25% of Muslims and 75% Christian. This study reveals the strengthening efforts of Islamic education conducted by Muslims in Sengkan the obstacles encountered and solutions to overcome the problems through a socio-psychological approach. This is a field research in the form of case studies. The Data obtained from observation, interview and documentation. The analysis is done by data reduction, data display, triangulation and conclusion drawing. The results show that there are three types of patterns of strengthening the Islamic education in Sengkan: first, through weekly religious activities (TPA for Children and Adults), second, selapanan (the religious meeting done in the mosque or house in Sunday night, Wednesday night, and Thursday night by the members of that area) and annual. Obstacles faced in weekly activities for the program of TPA for Children: (1) the development of age, (2) negative effects of technology, (3) the lack of human resources and the donation, as well as (4) the non strategic road access. Problems faced in the weekly activities TPA for Adult: (1) the concept of static activity, (2) the social factors (most of the members of the program are some busy adults), (3) economic factors (middle to lower), and (4) the lack of donation. Problems in holding the the selapanan activities are feeling lazy and troublesome. Barriers to annual activities are laziness and bothering, as well as a large activity budget. The solutions to those problems are: (a) for children's weekly activities (TPA for Children): the revitalization of Ramadhan, monitoring and fiterarization of any technology devices, empowering senior students, circulating religious donation for voluntary by bringing cans going around to every home, providing personal funding from takmir, and utilizing citizens' forums. (b) Solutions on TPA for Adult activities: inviting some speakers to discuss about a certain topic and to find some actual problem solvings, holding those activities in one of the members’ house, bringing own provisions, and donating some money through the turned cans to the houses. (c) Solutions for obstacles to the selapan activities: on Sunday Night (Pahing): using the official invitation and delivering some motivation to the members by the public figures. Evening Activities on Friday: made qurban through regular social gathering, approached when departing and giving motivation. Evening Activities on Friday (Pahing): giving some parcel on the way home and motivated by community leaders to members who are not active. While the solution to the obstacles of annual activity involves in committees and inappropriateness, motivated by figures and sustains funding needs (60% of society and 40% of takmir).